A LINGUISTIC ANALYSIS OF RHETORICAL MOVES IN WRITING REQUEST EMAILS AMONG UNIVERSITY STUDENTS - Faqe , Chiayee; Moheddin , Kurdistan (Humanities Journal of University of Zakho, 2025)
This study investigates the linguistic analysis of rhetorical moves of request strategies in writing emails among Kurdish university students engaged in an academic setting at Soran University. That is, how Kurdish university students structure and phrase request emails in English, focusing on the rhetorical moves they use to make their requests polite, clear, and persuasive. In fact, little is known about the specific challenges Kurdish university students face. By analyzing these students' rhetorical patterns, the study aims to improve our understanding of their communication needs and support more effective instruction for writing request emails in academic settings. This study adopts Swales' (1990) theory to analyze the data qualitatively and explore the rhetorical moves of request emails from a linguistic framework. For this purpose, fourteen emails were found in the researchers’ workplace emails. For the sake of data analysis, the researchers used a genre-based approach. All the email senders were Kurdish university learners of English as a foreign language. The findings revealed that though students tend to employ rhetorical moves, when communicating in English as a second language—especially when making requests via email. The current study also adds to the existing literature in the field of pure linguistics, offering insights into linguistic awareness that can be found in other scholarly works. It also highlights that Kurdish university students can easily communicate digitally in this technological era as academics once they acquire English language as a second language.